Sub-Saharan Africa : culture, history and people - Koku, Paul Sergius, 1955- (African studies, 2021)
"Sub-Saharan Africa literally remains the "gift that keeps giving". The more we know about this region of a rich and diverse continent, the less we realize that we actually knew. Thus, this book, Sub-Saharan Africa: Culture, History and People, is an effort to yet again revisit a region that we thought we knew. It is a culmination of eclectic research efforts, both conceptual and empirical, that focus on sub-Saharan Africa from scholars around the world. The book serves as useful compendium to those who already study the field and as an indispensable handbook to beginners who wish study the region"--